2011
DOI: 10.1002/srin.201000255
|View full text |Cite
|
Sign up to set email alerts
|

Wear Protection by Fe‐B‐C Hard Phases

Abstract: Four as-cast iron alloys with (mass%) 1B þ 3C, 2B þ 2C, 3B þ 1C and 4B þ 1C were investigated in respect to their microstructure by optical and scanning electron microscopy with EDX and ESBD and by microprobe analysis. The microhardness of eutectic Fe 3 (C,B) increased with the B/C ratio and raised the resistance to scratching by Flint particles. The low melting range of the castings was used for the powder metallurgical production of a metal matrix composite by liquid phase sintering of admixed hard particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Surface energy r in J/cm 2 Interface mobility l in cm 4 /(Js) Liquid c-Fe 0.2B to 1132°C in alloy 1.8B. At the same time, the liquidus temperature decreases with the B content from 1476°C in alloy 0.2B to 1332°C in alloy 1.8B.…”
Section: Phase Interactionmentioning
confidence: 95%
See 3 more Smart Citations
“…Surface energy r in J/cm 2 Interface mobility l in cm 4 /(Js) Liquid c-Fe 0.2B to 1132°C in alloy 1.8B. At the same time, the liquidus temperature decreases with the B content from 1476°C in alloy 0.2B to 1332°C in alloy 1.8B.…”
Section: Phase Interactionmentioning
confidence: 95%
“…Due to their stabilizing effect on the Fe 2 B phase, the elements Mn and Cr are also of high importance in the development of new Fe-C-B steels. With respect to the literature, it is known that Mn and Cr are enhancing the hardness and the fracture toughness of M 2 B phase (Fe 2 B $ 1500-1700 HV, 3.8 MPa m 1/2 -Cr 2 B $ 2000 HV, 7.8 MPa m 1/2 ) [2,4,34,35]. As an example, the influence of Cr on the stabilization of the Fe 2 B phase is illustrated in Fig.…”
Section: Application In Alloy Developmentmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous work (Chotěborský et al 2011) showed that increasing the volume fraction of eutectic carbides improves the abrasion resistance. Other possibility for increasing the abrasion resistance is the use of carbide forming element such as vanadium, tungsten, molybdenum or niobium into hardfacing metals (Berns 2003;Berns et al 2011). Especially niobium is an alloy which is currently used for creating microstructure of hardfacing with very hard niobium carbide (NbC) (Xiaohui et al 2008).…”
mentioning
confidence: 99%